Living Conditions in Retirement Homes in the Czech Republic and Austria from Seniors’ Point of View - Mathová, L.; Formánková, P. (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Senior citizens generally face more challenging life situations than other people (death of people close to them, deteriorating health, loss of social status, leaving home, etc.) – even multiple such situations at one time – and must cope with them. The focus of this report is one of these situations: the life of senior citizens in a retirement home, which is a type of residential social services. Objective: The objective of this research was to map the living conditions of seniors living in 1 retirement home in the Písek region (Czech Republic) and in 1 retirement home in the Innsbruck region (Austria). METHODS: The enquiry method was chosen for the research. A semi-standardised interview with 40 seniors was carried out as part of routine data collection. The topics of the interview were compiled as to cover areas related to residential standards, eating, economic situation, maintaining of social contacts, use of free time and assessment of health care. RESULTS: The research showed that both Czech and Austrian seniors assess their living conditions in the home as good. The respondents gave positive feedback on the clean environment, health and nursing care and the rate of participation in events organised in the homes. What the seniors found positive is maintaining social contacts and they prefer the availability of the above-standard service provided in the home. CONCLUSION: The research also showed that the reason for moving into the retirement home is primarily health problems and the related fear of compromised independence.